Condiciones de operación de la PPA del municipio de Manta, Cundinamarca. (2017)
The present work, it contains a general diagnosis on the physical and operative condition of the infrastructure arranged for the treatment of drinkable water of the municipality of Manta, with base to the primary and secondary existing information of his current condition. The Municipality of Manta does part of Almeidas's province, is located in Cundinamarca's department, approximately to the 05°00 ' 33 " of north latitude and 73°32 ' 29 " of length west, to a height on the level of the sea of 1.900 m. (Municipal mayoralty of Manta, 2016) Has a population of 4719 inhabitants. Nowadays, it possesses a system of treatment of drinkable water conventional type, his train of treatment consists of the following processes: coagulation, floculation, sedimentation, filtration and disinfection, the flow of design of the PPA is 15 LPS and produces 17 LPS.